Raising the iron curtain: Lactate's secret role in oxidative stress defense - Astrid Hensel; Renáta Váraljai; Shirley K. Knauer (Redox Biology)
The hypothesis presented here is that certain cell types under oxidative stress, such as cancer cells, reprogram their metabolism to accumulate lactate, along with cytosolic Fe2+ within the labile iron pool, thereby establishing a metabolite-based H2O2 detoxification system. In this scenario, the Fenton reaction between Fe2+ and H2O2 generates hydroxyl radicals (HO•), which are subsequently scavenged by abundant lactate. Thus, lactate production may function as a protective, iron-dependent antioxidant mechanism, enabling cells to decompose H2O2 and prevent damage to crucial biomolecules. If this system is compromised, for instance by inadequate HO•-scavenging or impaired Fe2+ recycling, cells may become prone to ferroptosis.